2001
DOI: 10.1051/0004-6361:20011240
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the local universe

Abstract: Abstract. The matter distribution around the Perseus-Pisces (PP) supercluster is studied by comparing peculiar velocities given by the Kinematics of the local universe (KLUN) galaxy sample to those predicted by Tolman-Bondi (TB) models. To restrict the TB solutions we first solve the mass of the densest part of PP. This part is identified as a sphere at (l, b) = (140.2• , −22.0Mpc having a radius of 15 h −1 Mpc. This sphere surrounds the main part of the PP ridge and four most prominent clusters of the region.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…He also asked what happens when the distances become more accurate, in particular, will the velocity dispersion still decrease below σ v = 60 km s −1 which he derived from those data. We also note that Karachentsev & Makarov (1996) found that by using both massive and small galaxies the velocity dispersion in the local volume is σ v = 72 km s −1 .…”
Section: Introductionmentioning
confidence: 57%
“…He also asked what happens when the distances become more accurate, in particular, will the velocity dispersion still decrease below σ v = 60 km s −1 which he derived from those data. We also note that Karachentsev & Makarov (1996) found that by using both massive and small galaxies the velocity dispersion in the local volume is σ v = 72 km s −1 .…”
Section: Introductionmentioning
confidence: 57%
“…Einasto et al 2011a, for an analysis of supercluster morphology). The collapsing high-density cores have been studied in the very rich Shapley and Corona Borealis superclusters (Reisenegger et al 2000;Pearson et al 2014), in the Perseus-Pisces supercluster (Hanski et al 2001;Teerikorpi et al 2015), in the A2199 supercluster, the member of the Hercules supercluster (Rines et al 2002;Einasto et al 2001), and also in the richest supercluster of the Sloan Great Wall (Einasto et al 2007(Einasto et al , 2011bHeinämäki et al, in prep.). Chon et al (2015) analysed the Shapley supercluster with the future collapse model and concluded that only the central part of the Shapley supercluster will form a supercluster in the distant future.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (e.g., (Karachentsev et al 2009)) use approximate formulas for M (R0). Now N-body simulations are frequently performed to obtain M (R0) (for example, (Hanski et al 2001;Peñarrubia et al 2014)). Of course, N-body simulations is a power method allowing to consider, e.g.…”
Section: Introductionmentioning
confidence: 99%